Mental Health in the Workplace. An international comparison of countries with different socioeconomic development A Case study of Mexico and the UK - Macias Espinoza, Maria Isabel (2020)
There is plenty of evidence from diverse disciplines that position mental health illness as a legitimate global concern. Undoubtedly, for all nations, mental health challenges should be a health priority, and many are failing to tackle this crisis (Boseley, 2018). In low-and-middle-income countries (LMIC) mental health interventions have been despairingly inadequate mainly due to its poor understanding (Patel, 2019). Each country varies in the administrative structures and legislation to respond to these issues (Gabriel & Liimatainen, 2000). Most evidence on mental health problems comes from developed countries (LaMontagne et al. 2016). While these studies have been disseminated globally, the resources available in LMICs are meagre (Sharan, Levav, Olifson, De Francisco, & Saxena, 2007). This is a problem given that national contexts are so different, and applying the research done by Western models to LMICs could be inappropriate. This finding served a motivation to make a comparison between developed and developing countries to disentangle the different aspects that are behind the policies of these countries and obtain additional knowledge of their contexts to support them in their mental health journeys adequately. This research makes an international comparison using Mexico and the United Kingdom (UK) as a case study. Both are OCDE (Organisation for Economic Co-operations and Development) members; the first one is a developed country and fifth-largest economy in the world. Mexico is in fifteen in that ranking and part of the developing county and LMIC classification (Desgardins, 2019). The overarching goal of this project is to make a country-level comparison of countries with different socio-economic development to understand what promotes and what hinders mental health at work. This project obtains data through a qualitative study interviewing HR professional in two countries which work mostly in MNCs (Multinationals). These practitioners provide current workplace trends from an organisational perspectives and information on their best practices and interventions. HR is recognised as the owner of embedding wellbeing in companies, so tapping into their expertise provides insights in understanding the discourse of each country's approach to supporting mental health at work and grasp their differences. HR professionals can also reveal knowledge on the labour legislation, work practices, and leaders and employee's attitudes on the topic. This information helps to uncover assumptions on cultural and social values as well as governance and institutional structures for both countries that either support or affect the mental health of the population. Additionally, this project also aims to find more on the changes brought by COVID-19 in the workplace, and how companies are dealing with the unprecedented trauma that this pandemic has posed to employee’s mental health. Several findings in Mexico and the UK show that different social and cultural aspects impact on the way they have advanced in opening conversations to reduce mental health stigma and provide adequate support and mental health care to its population. This study will also argue that countries attached a different meaning to mental health and wellbeing, therefore influencing strategies that organisations and governments need to take in consideration to improve their interventions. Gaps in both countries are also discussed which confirmed some assumptions that were found in the literature.